2014
DOI: 10.1002/ejp.621
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen/paracetamol: A history of errors, failures and false decisions

Abstract: Acetaminophen/paracetamol is the most widely used drug of the world. At the same time, it is probably one of the most dangerous compounds in medical use, causing hundreds of deaths in all industrialized countries due to acute liver failure (ALF). Publications of the last 130 years found in the usual databases were analyzed. Personal contacts existed to renowned researchers having contributed to the medical use of paracetamol and its precursors as H.U. Zollinger, S. Moeschlin, U. Dubach, J. Axelrod and others. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
101
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(104 citation statements)
references
References 87 publications
0
101
0
3
Order By: Relevance
“…In addition, reasons for the limited use of paracetamol in GER could be recent concerns and public discussions about the safety of paracetamol and its risks for hepatotoxicity [25]. At that time, the maximum quantity of paracetamol per package that can be purchased over-the-counter was limited in Germany and partially put under prescription-only medicine due to those discussions [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reasons for the limited use of paracetamol in GER could be recent concerns and public discussions about the safety of paracetamol and its risks for hepatotoxicity [25]. At that time, the maximum quantity of paracetamol per package that can be purchased over-the-counter was limited in Germany and partially put under prescription-only medicine due to those discussions [26].…”
Section: Discussionmentioning
confidence: 99%
“…At appropriate dose of APAP, NAPQI is generally eliminated through the conjugation with GSH. However, in overdosing conditions it depletes the systemic GSH levels causing hepato- and renal- toxicity [118]. Interestingly, a recent report demonstrated that even normal dose of APAP is linked to APAP-associated acute liver failure [119].…”
Section: Das: Protection Against Alcohol Analgesic Drugs and Othmentioning
confidence: 99%
“…While not generally considered an anti-inflammatory drug, acetaminophen (paracetamol, N-acetylpara-aminophenol, APAP) has similar clinical indications to NSAIDs due to its analgesic and antipyretic properties [18] . Acetaminophen inhibits the synthesis of prostaglandin (PG) E2, PGF2, and thromboxane B2 by lipopolysaccharide (LPS)-stimulated microglia, yet has no effect on the levels of pro-inflammatory mediators such as tumor necrosis factor (TNF)-α and NO [19,20] .…”
Section: Introductionmentioning
confidence: 99%